GEOCHEMICAL CLASSIFICATION AND CHARACTERIZATION OF THE BEACH SANDS OF ABU DHABI, UNITED ARAB EMIRATES: A COMBINATION OF CLUSTER AND DISCRIMINANT ANALYSIS - Al Rashedi, Saeed; Siad, Abdi (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Fifty seven beach sand samples were collected along the shoreline of Abu Dhabi, United Arab Emirates (UAE). The aim of the paper is to geochemically classify and characterize the beach sediments of Abu Dhabi. Their geochemical compositions were determined, using X-ray fluorescence analysis. A combination of cluster and discriminant analysis was applied to classify and characterize the beach sand. Cluster analysis produced a dendogram with two major beach sand types namely terrigenous and marine sand types. Each sand type were further subdivided into two and was characterized through discriminant. The terrigenous sand type was subdivided into allumino-silicate characterized by SiO2, Al2O3, K2O and TiO2 and heavy mineral-rich allumino-silicate through high content of Fe2O3, Cr2O3, MgO and MnO, while the marine sand type was subdivided into biogenic marine carbonate with high content of CaO and LOI and halite-rich biogenic carbonate marine sand types with Na2O in addition CaO and LOI. Through stepwise discriminant analysis it was possible to identify SiO2 and Fe2O3 as best discriminating geochemical variable for the four sand types by 100%.